2014
DOI: 10.1111/tpj.12578
|View full text |Cite
|
Sign up to set email alerts
|

Roothairless5, which functions in maize (Zea maysL.) root hair initiation and elongation encodes a monocot‐specificNADPHoxidase

Abstract: SUMMARYRoot hairs are instrumental for nutrient uptake in monocot cereals. The maize (Zea mays L.) roothairless5 (rth5) mutant displays defects in root hair initiation and elongation manifested by a reduced density and length of root hairs. Map-based cloning revealed that the rth5 gene encodes a monocot-specific NADPH oxidase. RNA-Seq, in situ hybridization and qRT-PCR experiments demonstrated that the rth5 gene displays preferential expression in root hairs but also accumulates to low levels in other tissues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 66 publications
5
104
0
Order By: Relevance
“…Finally, in situ mRNA hybridization experiments have shown that the transcription of HvPEROXIDASE45 is restricted to individual root epidermal cells (Kwasniewski et al, 2013a). In maize, the gene RTH5 encodes a grass species-specific NADPH oxidase; its loss-of-function mutation resulted in a marked drop in both RH density and RH length (Nestler et al, 2014). The phenotype can be related to a reduced accumulation of ROS in the trichoblasts.…”
Section: "Returning Were As Tedious As Go O'er": Rh Initiationmentioning
confidence: 99%
“…Finally, in situ mRNA hybridization experiments have shown that the transcription of HvPEROXIDASE45 is restricted to individual root epidermal cells (Kwasniewski et al, 2013a). In maize, the gene RTH5 encodes a grass species-specific NADPH oxidase; its loss-of-function mutation resulted in a marked drop in both RH density and RH length (Nestler et al, 2014). The phenotype can be related to a reduced accumulation of ROS in the trichoblasts.…”
Section: "Returning Were As Tedious As Go O'er": Rh Initiationmentioning
confidence: 99%
“…Two NOXs (AtNOXH and AtNOXJ) have been implicated in pollen tube tip expansion and fertilization (Boisson-Dernier et al, 2013;Kaya et al, 2014;Lassig et al, 2014) and one NOX (AtNOXC, named ROOT HAIR DEFECTIVE [RHD2]) in root hair tip growth (Fig 1; Foreman et al, 2003;Takeda et al, 2008). Recently, a monocot NOX named RTH5 (from maize [Zea mays]), with high sequence similarity to AtNOXH and AtNOXJ, was identified as an important player in the transition between root hair bulge formation and tip growth (Nestler et al, 2014).…”
Section: Apo Ros Homeostasis Is Regulated By Plasma Membrane Noxs Andmentioning
confidence: 99%
“…Several genes which affect root development in maize have also been identified: rtcs (rootless concerning crown and seminal roots), rth1 (roothairless 1), rth2 (roothairless 2), rth3 (roothairless 3), rth5 (roothairless 5) and rum1 (rootless with undetectable meristems 1). The gene rtcs controls crown root and seminal root formation [6] rth1, rth2, rth3, and rth5 control root hair elongation in maize [7][8][9][10], and rum1 controls lateral root growth and seminal root growth [11]. In addition, rth3 has also been shown to affect grain yield in maize [9].…”
Section: Introductionmentioning
confidence: 99%